Defining patterns of Sagittal Standing Posture in girls and boys of school age - Araújo, F (2017)
Background: Sagittal postural patterns are associated with back pain in adolescents and adults. However, whether postural patterns are already observable during childhood is unknown. Such a finding would confirm childhood as a key period for posture differentiation and thus for chronic pain etiology. Objective: The aims of this study were to identify and describe postural patterns in girls and boys of school age. Design: This was a cross-sectional study. Methods: Eligible children were evaluated at age 7 in the population-based birth cohort Generation XXI in Portugal. Posture was assessed through right-side photographs during habitual standing with retroreflective markers placed on body landmarks. Postural patterns were defined from trunk, lumbar, and sway angles with model-based clusters, and associations with anthropometric measures were assessed by multinomial logistic regression. Results: Posture was evaluated in 1,147 girls and 1,266 boys. Three postural patterns were identified: sway (26.9%), flat (20.9%), and neutral to hyperlordotic (52.1%) in girls and sway to neutral (58.8%), flat (36.3%), and hyperlordotic (4.9%) in boys. In girls, a higher body mass index was associated with a sway pattern (versus a flat pattern: odds ratio = 1.21; 95% CI = 1.12, 1.29), whereas in boys, a higher body mass index was associated with a hyperlordotic pattern (versus a flat pattern: odds ratio = 1.30; 95% CI = 1.17, 1.44). Limitations: Photogrammetry as a noninvasive method for posture assessment may have introduced some postural misclassifications. Conclusions: Postural patterns in 7-year-old children were consistent with those previously found in adults, suggesting that childhood is a sensitive period for posture differentiation. Sagittal morphology differed between girls and boys, emphasizing sex-specific biomechanical loads during a habitual upright position even in prepubertal ages.